THE URGENCE OF ISLAMIC EDUCATION IN EARLY CHILDREN - Darmansyah, Syahrani M. Thahir, Musta’an, Nurmaya Medopa, Irfandi (Novateur Publications, 2022)
In the era of globalization, humans must be able to compete because all opportunities are open to anyone. In pursuit of success in life, there will be fierce competition, therefore reliable Human Resources (HR) are needed, namely Human Resources who have expertise, tenacity, honesty and hard work. Human Resources who do not have these characteristics will lose the competition